Circuits of Memory: The War Memory Boom in Western Australia - Stephens, John (MDPI, 2012)
In some Australian academic circles in the 1980s it was believed that, as the numbers of soldiers of the world wars declined over time, so would attendances at war remembrance ceremonies on Anzac Day and interest in war commemoration in general. Contrary to expectation, however, there has been a steady rise in eagerness for war memory in Australia over the past three decades manifest in media interest and increasing attendance at Anzac Day services. Rather than dying out, ‘Anzac’ is being reinvented for new generations. Emerging from this phenomenon has been a concomitant rise in war memorial and commemorative landscape building across Australia fuelled by government funding (mostly federal) and our relentless search for a national story. Many more memorial landscapes have been built in Western Australia over the past thirty years than at the end of either of the World Wars, a trend set to peak in 2014 with the Centenary of Anzac. This paper examines the origins and progress of this boom in memorial building in Western Australia and argues that these new memorial settings establish ‘circuits of memory’ which ultimately re-enchant and reinforce the Anzac renaissance.